Trends in Hospital Billing for Mastectomy and Breast Reconstruction Procedures from 2013 to 2020 - Gong, Jung Ho; Koh, Daniel J.; Sobti, Nikhil; Mehrzad, Raman; Beqiri, Dardan; Maselli, Amy; Kwan, Daniel (Journal of Reconstructive Microsurgery, 2024)
Background With greater acceptance of postmastectomy breast reconstruction (PMBR) as a safe and reliable treatment option, the role of plastic surgeons in breast cancer management continues to rise. As Medicare reimbursements for surgical procedures decline, hospitals may increase charges. Excessive markups can negatively affect uninsured and underinsured patients. We aimed to analyze mastectomy and breast reconstruction procedures to gain insights into recent trends in utilization and billing.Methods We queried the 2013 to 2020 Medicare Provider Utilization and Payment Data with 14 Current Procedural Terminology (CPT) codes to collect service count numbers, hospital charges, and reimbursements. We calculated utilization (service counts per million female Medicare enrollees), weighted mean charges and reimbursements, and charge-to-reimbursement ratios (CRRs). We calculated total and annual percentage changes for the included CPT codes.Results Among the 14 CPT codes, 12 CPT codes (85.7%) with nonzero service counts were included. Utilization of mastectomy and breast reconstruction procedures decreased from 1,889 to 1,288 (−31.8%) procedures per million female Medicare beneficiaries from 2013 to 2020. While the utilization of immediate implant placements (CPT 19340) increased by 36.2%, the utilization of delayed implant placements (CPT 19342) decreased by 15.1%. Reimbursements for the included CPT codes changed minimally over time (−2.9%) but charges increased by 28.9%. These changes resulted in CRRs increasing from 3.3 to 4.4 (+33.3%) from 2013 to 2020. Free flap reconstructions (CPT 19364) had the highest CRRs throughout the study period, increasing from 7.0 in 2013 to 10.3 in 2020 (+47.1%).Conclusions Our analysis of mastectomy and breast reconstruction procedures billed to Medicare Part B from 2013 to 2020 showed increasingly excessive procedural charges. Rises in hospital charges and CRRs may limit uninsured and underinsured patients from accessing necessary care for breast cancer management. Legislations that monitor hospital markups for PMBR procedures may be considered by policymakers.
Keywords: breast reconstruction; mastectomy; billing; markup; breast cancer